Storytelling in Chefchaouen Northern Morocco : an Annotated Study of Oral Performance with Transliterations and Translations - Rahmouni, Aicha (Studies on performing arts & literature of the Islamicate world., 2015)
In Storytelling in Chefchaouen Northern Morocco Aicha Rahmouni offers two sets of tales told by two different storytellers, and an annotated study of the oral performance.